2009
DOI: 10.1007/s10327-009-0183-z
|View full text |Cite
|
Sign up to set email alerts
|

A new combination for the causal agent of tea anthracnose: Discula theae-sinensis (I. Miyake) Moriwaki & Toy. Sato, comb. nov.

Abstract: The causal agent of tea anthracnose, Gloeosporium theae-sinensis, was transferred to Discula based on morphological and molecular reidentification using living cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Moriwaki and Sato (2009) summarised the taxonomic history of this name and transferred G. theae-sinensis to Discula on the basis of DNA sequences. Sphaerella camelliae Cooke and its recombination Laestadia camelliae (Cooke) Berl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moriwaki and Sato (2009) summarised the taxonomic history of this name and transferred G. theae-sinensis to Discula on the basis of DNA sequences. Sphaerella camelliae Cooke and its recombination Laestadia camelliae (Cooke) Berl.…”
Section: Resultsmentioning
confidence: 99%
“…Other Colletotrichum species reported from tea include C. “ theae-sinensis ”, an invalid recombination of Gloeosporium theae-sinensis I. Miyake, proposed by Yamamoto ( 1960 ). Moriwaki and Sato ( 2009 ) summarised the taxonomic history of this name and transferred G. theae-sinensis to Discula on the basis of DNA sequences. Sphaerella camelliae Cooke and its recombination Laestadia camelliae (Cooke) Berl.…”
Section: Resultsmentioning
confidence: 99%
“…When the lower part of a swollen conidium, including the short germ tube, is hidden by the trichome it resembles an appressorium. Other appressoria, which are produced from conidia on cellophane film, have also been reported (Moriwaki & Sato 2009). However, such appressoria have never been observed, in earlier (Ando & Hamaya 1986) or present studies on trichomes.…”
Section: Discussionmentioning
confidence: 94%
“…Discula theae-sinensis (I. Miyake) Moriwaki & Toy. Sato [syn. Gloeosporium theae-sinensis I. Miyake, Colletotrichum theae-sinensis (I. Miyake) Yamamoto] causes anthracnose on tea [Camellia sinensis (L.) Kuntze], which is the most common disease in Japanese tea cultivation (Moriwaki & Sato 2009). Previous studies (Ando & Hamaya 1986, Hamaya 1982 have shown that D. theae-sinensis have a unique infection process.…”
Section: Introductionmentioning
confidence: 99%
“…Tea leaves are easily attacked by pathogens, leading to tree wilting and crop failure. There are many pathogens that attack tea plants, such as Colletotrichum spp., Pestalotiopsis spp., and Discula theae-sinensis 1 3 , of which Colletotrichum is the most important pathogenic genus. Colletotrichum species cause disease in an extremely wide range of hosts and live as endophytes in plants 4 .…”
Section: Introductionmentioning
confidence: 99%